2023
DOI: 10.6004/jnccn.2023.7027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Asian Race on Prognosis in De Novo Metastatic Prostate Cancer

Abstract: Background: Little is known about the impact of Asian race on the long-term survival outcomes of males with de novo metastatic prostate cancer (PCa). Understanding racial disparities in survival is critical for accurate prognostic risk stratification and for informing the design of multiregional clinical trials. Methods: This multiple-cohort study included individual patient-level data for males with de novo metastatic PCa from the following 3 cohorts: LATITUDE clinical trial data (n=1,199), the SEER program (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A recent NCDB analysis found significant differences among Asian American subgroups when compared with White patients, with most of these subgroups showing greater odds of presenting in a higher PCa risk group. 2 This disaggregation enables us to acknowledge the intricacies within different Asian communities. It may also allow better comparison of various Asian clinical trial cohorts and explain why certain trials do not find racial/ethnic differences in survival between Asian and White patients in the mPCa setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent NCDB analysis found significant differences among Asian American subgroups when compared with White patients, with most of these subgroups showing greater odds of presenting in a higher PCa risk group. 2 This disaggregation enables us to acknowledge the intricacies within different Asian communities. It may also allow better comparison of various Asian clinical trial cohorts and explain why certain trials do not find racial/ethnic differences in survival between Asian and White patients in the mPCa setting.…”
mentioning
confidence: 99%
“…3 Second, it is vital to further explore why Asian patients with PCa, despite often presenting at a higher stage, achieve better outcomes compared with their White counterparts. 2,4 Investigating this phenomenon could yield valuable information that benefits patients from all backgrounds. Although the finding that similarity between clinical trial and real-world data may suggest biologic distinctions unique to Asian individuals, we must also explore the possibility that the provision of care closer to that of clinical trials may explain the superior outcomes observed in their real-world Asian cohorts.…”
mentioning
confidence: 99%